Novel Application of Hydrotropic Solubilization in the Sectrophotometric Analysis of Tinidazole in Dosage Form - Maheshwari, R.K. (Asian Journal of Chemistry, 2010)
In the present investigation, tinidazole has been selected as a poorly water-soluble model drug. There was more than 60, 70 and 105 fold enhancement in aqueous solubility of tinidazole by 1.25 M sodium citrate, 4 M sodium acetate and 8 M urea solutions (as compared to aqueous solubility), respectively. These hydrotropic agents were employed to solubilize the drug from the fine powder of tablet formulations. The selected λmax for spectrophotometric estimation was 318 nm. The hydrotropic agents and the additives used in the manufacture of tablets did not interfere in the analysis. Proposed method is new, rapid, simple, accurate and reproducible. Statistical data proved the accuracy, reproducibility and the precision of the proposed method.